KONTRIBUSI EKSTRAKURIKULER BOLABASKET TERHADAP PEMBIBITAN ATLET DAN PENINGKATAN KESEGARAN JASMANI - Hastuti, Tri Ani (Jurnal Pendidikan Jasmani Indonesia, 2011)
<p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 79.4pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 240.7pt; mso-height-rule: exactly;">Abstract <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">The idea that physical education is to improve physical <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">fitness is impossible because the limited time <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">provided in secondary high school curriculum. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Therefore, the policy to have sports as extracurricular <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">is important which are driven to provide programs <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">based on students’ interest, talents, situation, and <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">needs. Basketball as an extracurricular contributes <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">to improve students’ physical fitness and also talent <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">scouting. Regular and systematic exercise will <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">improve physical fitness components such as : (1) <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">cardiorespiratory endurance, (2) muscle strength and <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">endurance, (3) flexibility, (4) body composition. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Basketball as an extra curricular program functions <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">as development of basketball elite athletes. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 463.8pt; mso-height-rule: exactly;">Kata kunci : ekstrakurikuler bolabasket, pembibitan, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.65pt; mso-element-top: 463.8pt; mso-height-rule: exactly;">kesegaran jasmani.